Analysis of National Library of Medicine (NLM) DOCLINE® Interlibrary Loan System Request Patterns during Selected Public Health Events. Issue 3 (15th July 2021) - Hochstein, Colette; Han, Sharon; Juneau, Paul; Takamaru, Gillian; Unger, Elisabeth
Abstract: DOCLINE®, the U.S. National Library of Medicine's (NLM) interlibrary loan (ILL) request system, sought to better understand its role in providing information access during public health events (PHEs). Such data can guide service improvement, especially when connecting the public health community to the latest research during such incidents. Four U.S. public health outbreaks were used to measure DOCLINE's capacity to support information seeking behaviors: requests during the Summer 2019 measles outbreak; the Fall 2019 e-cigarette lung injury event; the 2018–2019 influenza season; and early stages of the 2020 COVID-19 outbreak. NLM Medical Subject Headings were used to identify related requests. A team of NLM librarians analyzed these for trends in request volume, geographic and institution type, and content. While the number of PHE-related requests did not make up a large percentage of the total placed, there were identifiable increases during the selected periods. These originated from a variety of geographic locations, with some noticeable intersection with outbreak areas. Hospitals initiated the most requests. This investigation provides evidence that DOCLINE data can be used to drive system development and that a targeted ILL system with rapid turnaround times is an especially valuable library resource during PHEs. Supplemental data for this article is available online at https://doi.org/10.1080/1072303X.2021.1934216 .